Faktor yang Mempengaruhi Kecurangan Laporan Keuangan di Badan Usaha Milik Negara Indonesia - Abriatika, Farrasnanda Noni; Mutmainah, Siti (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
The research objective was to analyze empirically the influence of pressure, opportunity, rationalization and capability factors on fraudulent financial statements. Cases of fraudulent financial statements that caused substantial losses for many parties prompted research to be carried out. The object in this study is a State Owned Enterprise. The purposive sampling technique in this study resulted in 268 observations. The research method is quantitative, and the analysis used is logistic regression. The results showed that ROA had a negative effect on the occurrence of financial statement fraud, while the proportion of KI, auditor turnover, and CEO tenure did not affect the occurrence of financial statement fraud. Research contributes to various parties as a material consideration in assessing information that may influence the occurrence of fraudulent financial statements. Keywords: Fraud Diamond Theory; Return on Assets; Independent Commissioners; Auditor Changes; CEO Tenure